Pengaruh Motivasi Hedonis dan Gaya Hidup Terhadap Perilaku Belanja Online di Marketplace pada Generasi Z di Kabupaten Karawang - Nurazizah, Runi; Isyanto, Puji; Sumarni, Neni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The continuous growth of internet users has triggered major changes in online shopping behavior, where people are switching from conventional shopping to online shopping. Online shopping behavior is the process of purchasing products or services via the internet. The growth of e-commerce in Indonesia, especially through online marketplaces. This research aims to determine the relationship between hedonic motivation and lifestyle on Generation Z's online shopping behavior. By applying the Hair et al formula in the analysis. The sample selected was 90 respondents. The data obtained from the questionnaire was then analyzed using validity and reliability tests, classical assumption tests and hypothesis tests using SPSS software. The results of this study show that hedonic motivation has a significant negative effect on online shopping behavior, and lifestyle has a significant positive effect on online shopping behavior in the market.